Strategic marketing management cases - Cravens, David W.; Lamb, Charles W., Jr.; Crittenden, Victoria L. (New York Richard D Irwin, 1995)
Focusing on the major decision-making challenges facing marketing managers in the late 1990s, this text's cases include a broad range of companies. It reflects marketing management priorities: market orientation, growth strategies, and target market strategies.
Keywords: management; marketing